Vitamin D deficiency and diabetic retinopathy risk in patients with newly diagnosed type 2 diabetes mellitus: a retrospective analysis - Hung, Kuo-Chuan; Chang, Li-Chen; Chang, Ying-Jen; Ho, Chun-Ning; Wu, Jheng-Yan; Liu, Wei-Cheng; Chen, I-Wen (Frontiers in Nutrition, 2025)
BackgroundVitamin D deficiency (VDD) has emerged as a potential contributor to diabetic complications. This study aimed to investigate the association between VDD at the time of type 2 diabetes mellitus (T2DM) diagnosis and subsequent risk of developing diabetic retinopathy (DR).MethodsThis retrospective cohort study used data from the TriNetX Research Network to analyze adult patients newly diagnosed with T2DM between January 2020 and December 2022. The patients were classified as vitamin D-deficient (<20 ng/mL) or sufficient (≥30 ng/mL). After 1:1 propensity score matching, 10,651 patients were included in each group. The primary outcome was the risk of DR within 3 years of T2DM diagnosis. The secondary outcomes included hospitalization, emergency department visits, pneumonia, and all-cause mortality. An exploratory analysis was also conducted to examine outcomes in patients with vitamin D insufficiency (20–30 ng/mL) compared to the sufficient group.ResultsAt the 3-year follow-up, VDD was significantly associated with an increased risk of DR [hazard ratio (HR) 1.45, 95% confidence interval (CI) 1.17–1.80, p < 0.001], hospitalization (HR 1.23, 95% CI 1.17–1.29, p < 0.001), emergency department visits (HR 1.17, 95% CI 1.11–1.24, p < 0.001), pneumonia (HR 1.18, 95% CI 1.07–1.31, p = 0.001), and mortality (HR 1.51, 95% CI 1.36–1.67, p < 0.001). Sex-stratified analysis revealed that the association between VDD and DR was significant among female patients (HR 1.41, 95% CI 1.07–1.86, p = 0.015) but not among males. Exploratory analysis showed that vitamin D insufficiency (20–30 ng/mL) was not associated with increased DR risk, suggesting a threshold effect.ConclusionIn newly diagnosed T2DM patients, VDD was independently associated with increased risks of DR and other adverse outcomes, particularly in females. The observed threshold effect suggests that maintaining vitamin D levels above the deficiency threshold may be sufficient to mitigate DR risk. Assessment of vitamin D status may be valuable for risk stratification in newly diagnosed T2DM, and addressing VDD may represent a modifiable risk factor for improving outcomes.